وقف النقود وحوكمته في جمعية العون المباشر : دراسة تحليلية مقاصدية - أحمد، هدى يعقوب (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Though offering favour to others is the nature of man in all human societies, the comprehensive meaning of endowment was formulated only upon the dawn of Islam in the city of Medina. Its objectives and purposes varied as the Prophet (peace be upon him) encouraged his companions to practice endowment and thus, they answered his call. Endowment continued to grow and earned more and more attention throughout the ages. Muslim scholars paid great attention to studying endowment and contemporary studies subsequently followed to explore ways of promoting and developing endowment to keep pace with the requirements of modern time. Despite the efforts that have been exerted to revive Islamic endowment which severely suffers from great negligence and a state of stagnancy and interruption of its benefits and its inability to keep pace with the development that we live today especially with the evolution of some transactions and economic conditions that created new styles of transactions compared to conventional endowment, it is necessary to study other endowments which are more viable and beneficial in the modern time such as money and stocks endowment, benefits, and moral rights. The research addresses the issue of money endowment and aims to explain the reality of money endowment and its relevant issues and rulings, and to discuss scholars' opinions with special emphasis upon the practical application of money endowment, the educational endowment in particular in Direct Aid Foundation (Kuwait) and how it is governed, as well as explaining the importance of this kind of endowment and its ability to develop the Islamic communities and their economies in the future especially marginalized African countries. The researcher adopted both the inductive and analytical approaches and conducted some field questions by interviewing some individuals concerned with the educational endowment in Direct Aid Foundation. The researcher came up with some findings of which the most important includes the permissibility of money endowment and that this type of endowment has great significance to the development of societies. Money endowment proved its success through the experience of Direct Aid Foundation which coped with poverty and illiteracy in most African countries.